The Elizabethan Stage, 1. - Chambers, E. K. (OUP Oxford, 2009)
First volume of a reissue of the E.K. Chambers's seminal four-volume account of the private, public, and court stages, together with other forms of drama and spectacle surviving from earlier times, from the beginning of the reign of Elizabeth until the death of Shakespeare. Haled in its day as a comprehensive compendium of 'practically all the discoverable evidence upon the various parts of the subject, collected, weighed, sorted, classified and built up with immense care into alogical and beautiful structure' (New Statesman), the work is still much consulted by today's scholars and histor.